Homoplasy in the evolution of modern human-like joint proportions in Australopithecus afarensis - Anjali M Prabhat (eLife Sciences Publications Ltd, 2021)
The evolution of bipedalism and reduced reliance on arboreality in hominins resulted in larger lower limb joints relative to the joints of the upper limb. The pattern and timing of this transition, however, remains unresolved. Here, we find the limb joint proportions of Australopithecus afarensis, Homo erectus, and Homo naledi to resemble those of modern humans, whereas those of A. africanus, Australopithecus sediba, Paranthropus robustus, Paranthropus boisei, Homo habilis, and Homo floresiensis are more ape-like. The homology of limb joint proportions in A. afarensis and modern humans can only be explained by a series of evolutionary reversals irrespective of differing phylogenetic hypotheses. Thus, the independent evolution of modern human-like limb joint proportions in A. afarensis is a more parsimonious explanation. Overall, these results support an emerging perspective in hominin paleobiology that A. afarensis was the most terrestrially adapted australopith despite the importance of arboreality throughout much of early hominin evolution.